Kekuatan Keterangan Ahli Terhadap Alat Bukti Elektronik Dalam Perkara Perdata - Alifa Ramadhani Adrianti; Reni Anggraini (Universitas Muhammadiyah Yogyakarta, 2024)
This writing aims to find out how the strength of expert testimony on electronic evidence in court, the method used in writing is normative juridical or literature, which is carried out by literature study of legal materials. with the development of the times electronic products are increasingly sophisticated and developed, humans can find applications or web editing easily so it is very possible to falsify electronic information. Electronic evidence must be recognised in order to have binding legal force, if it is not recognised, other evidence is needed as stated in article 1866 of the Civil Code / article 164 HIR regarding types of evidence including expert testimony. Expert testimony is still very much needed to provide an understanding of a civil case, especially in situations that are beyond the expertise or scientific knowledge of the judge. It can be concluded with certainty that the information provided by an expert is not considered as evidence, but rather serves to strengthen the strength of existing evidence. Therefore, it cannot determine the outcome of a civil court decision. The Panel of Judges can still consider and make decisions on existing issues even without expert opinion.